Mechanical properties of M-Zr (M=Cr, Al, Mn) co-doped ceria: A first-principles study. Issue 1 (February 2021) - Xiao, Wei; Shi, Jingmin; Sun, Lu; Wang, Xue; Zhou, Gege; Yan, Jiasi
Abstract: Zr-doped ceria has been extensively been used in three-way catalyst industry due to the excellent physical and chemical properties. Co-doping technology is always employed to improve the stability of the materials by hindering the phase segregation into CeO2 and ZrO2 individual phases. In this paper, we have intensively studied the stability of M-Zr co-doping systems (M= Cr, Al and Mn) under different growth conditions and under the applied stress. The results show that the O-rich growth condition is very beneficial to the formation of these compounds. Compared with Cr and Mn atoms, Al atoms produce a different type of lattice distortions, which all can improve the stability of the whole system. Among these candidates, Al-Zr co-doping can be most easily formed. Furthermore, our researches demonstrate that under a small strain range, co-doping might increase the mechanical properties of the systems by the solid solution strengthening.